TYPES OF INNOVATION IN THE CONDITIONS OF INTERNATIONAL ECONOMIC RELATIONS - Verbytska , H.L. (The actual problems of regional economy development, 2018)
The purpose of the article is to develop a classification of innovations of enterprises that operate in conditions of international economic relations. In the process of research, the following methods were used: tabular (for visual presentation of the research results); analytical and structural-logical (in developing the classification of innovations). The following results are obtained: the classification of innovations is proposed, which includes generalized main features and types of innovations; the essence of each of the innovations and its own qualitative characteristics are determined. The scientific novelty of the study is to use a comprehensive approach to substantiating key features and types of enterprise innovations. The obtained results can be used in the process of formation of an innovative strategy of the enterprise in the conditions of international economic relations.